Ablation of SIRT3 causes coronary microvascular dysfunction and impairs cardiac recovery post myocardial ischemia. (15th July 2016) - He, Xiaochen; Zeng, Heng; Chen, Jian-Xiong
Abstract: Rationale: Sirtuin (SIRT3), a major nicotinamide adenine dinucleotide (NAD + )-dependent deacetylase in mitochondria, declines with aging and its ablation is associated with accelerated development of cardiovascular diseases. However, the role of SIRT3 in coronary microvascular function and post-MI recovery has not been completely understood. Objective: The goal was to investigate whether ablation of SIRT3 causes coronary microvascular dysfunction, exacerbates post-myocardial ischemia (MI) cardiac dysfunction and impairs cardiac recovery. Methods and results: Using endothelial cells (ECs) isolated from SIRT3 knockout (KO) mice, we revealed that the angiogenic capabilities were significantly reduced in SIRT3 deficient ECs. SIRT3 KO mice presented a pre-existing coronary microvascular dysfunction and microvascular rarefaction, as evidenced by a reduction in hyperemic peak diastolic blood flow velocity and coronary flow reserve (CFR), accompanied by loss of capillary-pericytes in the heart. Furthermore, SIRT3 KO mice subjected to myocardial ischemia by the ligation of left anterior descending coronary artery (LAD) exhibited more severe cardiac dysfunction together with decreased pericyte/EC coverage than that of wild type (WT) mice. In contrast, overexpression of SIRT3 preserved cardiac function in post-MI mice. Immunoblot analysis further showed that the expression of angiopoietin-1 (Ang-1), vascular endothelial growth factor (VEGF) and 6-phosphofructo-2-kinase/fructose-2, 6-biphosphatase 3 (PFKFB3) were significantly decreased in the SIRT3-deficient ischemic hearts than those of WT ischemic hearts. This was accompanied by higher levels of cleaved caspase-3 and apoptosis. Conclusion: Our results reveal a potential mechanism by which SIRT3 deletion exacerbates post-MI cardiac dysfunction and impairment of cardiac recovery involving microvascular rarefaction and pre-existing coronary microvascular dysfunction. Highlights: SIRT3 deficiency leads to decreased CFR and microvascular dysfunction. SIRT3 deficiency exacerbates post-MI cardiac dysfunction and impairment of cardiac recovery. Overexpression of SIRT3 attenuates myocardial ischemia induced cardiac dysfunction.